2021
DOI: 10.1038/s41477-021-00932-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic promoter designs enabled by a comprehensive analysis of plant core promoters

Abstract: Targeted engineering of plant gene expression holds great promise for ensuring food security and for producing biopharmaceuticals in plants. However, this engineering requires thorough knowledge of cis-regulatory elements in order to precisely control either endogenous or introduced genes. To generate this knowledge, we used a massively parallel reporter assay to measure the activity of nearly complete sets of promoters from Arabidopsis, maize and sorghum. We demonstrate that core promoter elements -notably th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
140
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(150 citation statements)
references
References 75 publications
9
140
1
Order By: Relevance
“…Preliminary experiments building similar regulatory programs in bacteria and mammalian cell lines suggests that some of the basic design rules for regulatory circuits may apply in both prokaryotes and eukaryotes ( Tigges et al, 2009 ; Stanton et al, 2014 ). Plus, new molecular tools for controlling transcription and translation in plants, such as synthetic promoters ( Cai et al, 2020 ; Jores et al, 2021 ), polyadenylation signals ( Felippes et al, 2020 ; Andreou et al, 2021 ), and transcription factors ( Schaumberg et al, 2016 ; Belcher et al, 2020 ), are being developed at break neck speeds. Additional tools that improve our control over gene expression in plants will be needed to create synthetic developmental regulation (Outstanding Questions Box).…”
Section: Engineering Auxin-insensitive Developmentmentioning
confidence: 99%
“…Preliminary experiments building similar regulatory programs in bacteria and mammalian cell lines suggests that some of the basic design rules for regulatory circuits may apply in both prokaryotes and eukaryotes ( Tigges et al, 2009 ; Stanton et al, 2014 ). Plus, new molecular tools for controlling transcription and translation in plants, such as synthetic promoters ( Cai et al, 2020 ; Jores et al, 2021 ), polyadenylation signals ( Felippes et al, 2020 ; Andreou et al, 2021 ), and transcription factors ( Schaumberg et al, 2016 ; Belcher et al, 2020 ), are being developed at break neck speeds. Additional tools that improve our control over gene expression in plants will be needed to create synthetic developmental regulation (Outstanding Questions Box).…”
Section: Engineering Auxin-insensitive Developmentmentioning
confidence: 99%
“…Moreover, recent evidence indicated that AtUBQ10 promoter was more stable and persistent than CaMV 35S in Arabidopsis, tobacco and rice ( Grefen et al, 2010 ; Behera et al, 2015 ; Peramuna et al, 2018 ; Wang et al, 2021 ). While few studies have demonstrated that plant-derived promoters display similar efficacies in driving gene expression in both monocot and dicot species, not all promoters behave similarly ( Christensen et al, 1992 ; Behera et al, 2015 ; Jores et al, 2021 ). This necessitates comparing the activity of plant promoters derived from both monocots and dicots to be tested within an assay.…”
Section: Introductionmentioning
confidence: 99%
“…However, baring studies by Beringer et al (2017) and Feike et al (2019) , most studies did not compare plant-derived constitutive promoters from various species within a single assay. Besides, plant-derived constitutive promoters, another excellent option to achieve robust and precise expression is the usage of synthetic promoters ( Peramuna et al, 2018 ; Ali and Kim, 2019 ; Cai et al, 2020 ; Jores et al, 2021 ). Since synthetic promoters are assembled linking cis -regulatory elements of various promoter regions upstream of the core promoter (TATA box), one can combine tissue specificity with heightened expression within the same promoter construct.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations